Pulmonary Tuberculosis and Rifampicin Resistant Mycobacterium Tuberculosis in Children and Adolescents using Gene Xpert MTB/RIF Assay in Tigray, Northern Ethiopia - Dejene TA; Hailu GG; Kahsay AG; Wasihun AG (Infection and Drug Resistance, 2023)
Tsehaye Asmelash Dejene,1,2 Genet Gebrehiwet Hailu,1 Atsebaha Gebrekidan Kahsay,1 Araya Gebreyesus Wasihun1 1Department of Medical Microbiology and Immunology, School of Medicine, College of Health Sciences, Mekelle University, Mekelle, Ethiopia; 2Department of Medical Microbiology, School of Medicine, Aksum University, Axum, EthiopiaCorrespondence: Atsebaha Gebrekidan Kahsay, Department of Medical Microbiology and Immunology, School of Medicine, College of Health Sciences, Mekelle University, P. O. Box: 1871, Mekelle, Tigrai, Ethiopia, Email atsebaha.gebrekidan@mu.edu.etBackground: Tuberculosis (TB) continues to be a global health problem. While childhood TB contributes 10% to the global TB burden, the paucibacillary nature of TB disease in children and the absence of reliable diagnostic methods have made MTB diagnosis in children to be a great challenge. This study aimed to determine the prevalence of MTB and rifampicin-resistant MTB (RR-MTB) among children using Gene Xpert MTB/RIF Assay in Tigray, Ethiopia.Methods: A retrospective database study was conducted among children in ten governmental hospitals in the Tigray region. Gene Xpert MTB/RIF results of sputum/gastric lavage samples from children with presumptive TB from January 2016 to December 2019 were extracted using a data extraction sheet. Data were collected and analyzed using Statistical Package for the Social Sciences version 21.Results: The prevalence of bacteriologically confirmed MTB by Gene-Xpert in children with presumptive TB was 7.3% (95% CI: 6.7%− 7.9%) and the proportion of those that were Gene-Xpert MTB positive who also have rifampicin resistance was 10.9% (95% CI: 8.2– 13.6%). Older children aged 11– 15 years [AOR = 1.76; 95% CI = 1.33– 2.33, p < 0.001] and adolescents 16– 17 years [AOR = 2.18; 95% CI = 1.63– 2.92, p < 0.001] were more likely to be MTB positive. Relapse cases [AOR = 1.66; 95% CI = 1.09– 2.51, p = 0.017] and lost/failure cases [AOR = 8.82; 95% CI = 3.94– 19.76, p < 0.001] were more likely to have MTB compared to the new cases.Conclusion: The proportion of MTB-positive among the TB presumptive patients was 7.3%. The proportion of rifampicin-resistant TB to all positive patients was 10.9%. Female participants had more MTB than males (or younger children). The result highlights the need for due attention in children because it is very helpful in determining the future control of the disease.Keywords: children and adolescent, presumptive TB, rifampicin resistant, Xpert MTB/RIF, Tigray, Ethiopia